The Relationship Basic Knowledge of The Art of Design And Student Creativity With Make Up Character Competence - Vita Pujawanti Dhana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
This research aims to determine and analyze the relationship between Basic Knowledge of Design Art and Creativity with Character Make-up Competence of Student. This research is classified as quantitative research with a correlational approach. The sample in this research amounted to 26 people with a saturated sample technique. The data is taken through a questionnaire arranged with a Likert scale that has been tested for validity and reliability. First result, testing the first hypothesis stated that there was a positive relationship between basic knowledge of the art of design and the competence of character makeup. This is indicated by a simple linear regression equation = 48.66 + 0.388 which has been tested for significance at = 0.05. Furthermore, through the results of a simple correlation test, the correlation ry1 is 0.604 and the coefficient of determination r2y1 is 0.364. This means that 36.4% of the character's makeup competence is determined by the basic knowledge of the art of design. Second, the results of testing the second hypothesis state that there is a positive relationship between creativity and character makeup competence. This is indicated by a simple linear regression equation = -9.75 + 0.984 X2 which has been tested for its significance at = 0.05. Furthermore, through the results of a simple correlation test, it was obtained that the ry2 correlation was 0.728 and the coefficient of determination r2y2 was 0.575. This means that 57.5% of the character's makeup competence is determined by creativity. Third, the results of testing the third hypothesis state that there is a positive relationship between basic knowledge of design art and creativity together with character makeup competence.